Long period grating cascaded to photonic crystal fiber modal interferometer for simultaneous measurement of temperature and refractive index - Hu, Dora Juan Juan (2013)
We propose and demonstrate a novel and simple dual-parameter measurement scheme based on a cascaded optical fiber device of long-period grating (LPG) and photonic crystal fiber (PCF) modal interferometer. The temperature and refractive index (RI) can be measured simultaneously by monitoring the spectral characteristics of the device. The implemented sensor shows distinctive spectral sensitivities of −30.82  nm/RIU (refractive index unit) and 47.4  pm/°C by the LPG, and 171.96  nm/RIU and 10.4  pm/°C by the PCF modal interferometer. The simultaneous measurement of the temperature and external RI is experimentally demonstrated by the sensor. The temperature shift and RI shift calculated by the sensor matrix agree well with the actual temperature and RI change in the experiment.